A Rare Case of Conjunctival Melanoma with Orbital Invasion - Guerra-Perez, Lina Maria; Bonilla-Escobar, Francisco J.; Salamanca, Omar; Martínez-Blanco, Alexander; Alarcon-Arciniegas, Carolina (Nepalese Journal of Ophthalmology, 2020)
Letter to the editor about disparities in healthcare, despite that Nepal and Colombia are countries with very different economies both have patients with eye tumors in advanced stages without adequate follow-up such as the one described in the case in discussion.